2011
DOI: 10.1249/mss.0b013e318212a317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of l-Arginine Infusion on Glucose Disposal during Exercise in Humans

Abstract: The increase in glucose disposal after l-Arg infusion during exercise is likely due to the significantly higher plasma insulin concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
(61 reference statements)
3
16
0
Order By: Relevance
“…Linden et al (2011) reported increased plasma insulin concentration during exercise with L-arginine supplementation, which would decrease endogenous glucose production, increase exogenous glucose disposal and oxidation by skeletal muscle, and lower fat oxidation (Costill et al 1977), consistent with the present data. Upon publication of the Linden et al study (2011), we attempted to measure insulin concentrations in the 3 year stored blood plasma samples from the current study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Linden et al (2011) reported increased plasma insulin concentration during exercise with L-arginine supplementation, which would decrease endogenous glucose production, increase exogenous glucose disposal and oxidation by skeletal muscle, and lower fat oxidation (Costill et al 1977), consistent with the present data. Upon publication of the Linden et al study (2011), we attempted to measure insulin concentrations in the 3 year stored blood plasma samples from the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this notion, intestinal vasodilation was only observed in those conditions where sodium and water absorption were increased (Wapnir et al 1997). Furthermore, L-arginine infusion increased leg glucose clearance during exercise (McConell et al 2006), which could be due to an increase in NO production (Bradley et al 1999) or to increased plasma insulin concentration (Linden et al 2011). While these data are all from animal studies, a question on similar effect in humans can be logically raised.…”
Section: Introductionmentioning
confidence: 74%
“…A recent study by Totzeck et al (38) has shown that plasma nitrite concentration is related to exercise capacity in moderate trained subjects. This finding could also be related to an increase of nitrite throughout NOS activity because there is evidence that endurance exercise stimulates skeletal muscle NOS function in humans during exercise (24). Regarding the above studies with nitrate supplementation, study by Cermak et al (7) did not analyze plasma levels of nitrite, and consequently, it is not possible to know whether all subjects responded equally to nitrate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide synthase (NOS) activity and/or NO production increases during contraction of muscle cells (Silveira et al 2003;Pattwell et al 2004), ex vivo skeletal muscle contraction (Balon & Nadler, 1994;Merry et al 2010a,b), in situ muscle contraction (Ross et al 2007), treadmill exercise in rodents and cycling exercise in humans (Roberts et al 1999;Linden et al 2011;Fig. 1).…”
Section: Nitric Oxide Production During Contractionmentioning
confidence: 99%